System Design and Application of Supercritical and Transcritical CO2 Power Cycles: A Review - Wang, Enhua; Peng, Ningjian; Zhang, Mengru (Frontiers in Energy Research, 2021)
Improving energy efficiency and reducing carbon emissions are crucial for the technological advancement of power systems. Various carbon dioxide (CO2) power cycles have been proposed for various applications. For high-temperature heat sources, the CO2 power system is more efficient than the ultra-supercritical steam Rankine cycle. As a working fluid, CO2 exhibits environmentally friendly properties. CO2 can be used as an alternative to organic working fluids in small- and medium-sized power systems for low-grade heat sources. In this paper, the main configurations and performance characteristics of CO2 power systems are reviewed. Furthermore, recent system improvements of CO2 power cycles, including supercritical Brayton cycles and transcritical Rankine cycles, are presented. Applications of combined systems and their economic performance are discussed. Finally, the challenges and potential future developments of CO2 power cycles are discussed. CO2 power cycles have their advantages in various applications. As working fluids must exhibit environmentally-friendly properties, CO2 power cycles provide an alternative for power generation, especially for low-grade heat sources.